Comparative Outcomes of Open vs. Endoscopic Carpal Tunnel Release: Our Experience in a Tertiary Hospital - Ali Manzoor, Shakeel Ahmed, Muhammad Irshad, Atta Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate and compare the clinical outcomes of open carpal tunnel release (OCTR) and endoscopic carpal tunnel release (ECTR) in patients undergoing surgery for carpal tunnel syndrome (CTS) at a tertiary care hospital. Methods: A retrospective cohort study was conducted involving 80 patients who underwent either OCTR or ECTR for CTS between July 2022 and June 2023. Patient demographics, operative details, and postoperative outcomes were analyzed. Functional outcomes were assessed using the Boston Carpal Tunnel Questionnaire (BCTQ), grip strength measurements, and patient satisfaction surveys. Results: Of the 80 patients, 40 underwent OCTR and 40 underwent ECTR. The ECTR group demonstrated significantly shorter operative times (mean 22 minutes vs. 35 minutes, p<0.001) and earlier return to work (mean 7 days vs. 14 days, p<0.001). Postoperative pain levels were lower in the ECTR group (mean Visual Analog Scale score 2.1 vs. 3.4, p<0.01). However, the OCTR group had a lower incidence of complications, including nerve injury (1% vs. 4%, p=0.03) and wound infection (0% vs. 2%, p=0.04). Conclusion: Both OCTR and ECTR are effective surgical options for the treatment of CTS. ECTR offers advantages in terms of shorter operative time and quicker return to work, but is associated with a higher incidence of certain complications. The choice of surgical technique should be individualized based on patient factors and surgeon expertise. Keywords: Open carpal tunnel release, endoscopic carpal tunnel release, carpal tunnel syndrome, surgical outcomes, postoperative recovery.